COMPARATIVE ANALYSIS OF METAPHORICAL PATTERNS (Multidisciplinary Journal of Science and Technology, 2024)
This article explores the intricate dynamics of metaphorical patterns through a comparative lens, examining their usage across diverse contexts, languages, cultures, and domains. Beginning with a foundational understanding of metaphor's role in decision-making processes and cognitive frameworks, it delves into the profound relationship between metaphor and cultural identity. Drawing on insights from cultural linguistics, anthropology, and metaphor studies, the discussion navigates through the nuanced ways in which culture influences the creation, interpretation, and significance of metaphors. Comparative analyses across various dimensions, including linguistic, cognitive, temporal, and technological, offer a comprehensive view of how metaphorical expressions shape communication, cognition, and cultural understanding. Through methodologies such as cross-linguistic studies, domain-specific analyses, and discourse comparisons, researchers illuminate the multifaceted nature of metaphor and its pervasive impact on human thought and expression.